2018
DOI: 10.1155/2018/8284107
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Taraxasterol against Ethanol‐Induced Liver Injury by Regulating CYP2E1/Nrf2/HO‐1 and NF‐κB Signaling Pathways in Mice

Abstract: Taraxasterol, a pentacyclic-triterpene compound, is one of the main active components isolated from the traditional Chinese medicinal herb Taraxacum. The objective of this study is to evaluate the protective effects of taraxasterol and its possible underlying mechanisms against ethanol-induced liver injury in mice. ICR mice were fed with Lieber-DeCarli diet containing 5% ethanol for 10 d and then challenged with a single dose of 20% ethanol (5 g/kg BW) by intragastric administration. The mice were intragastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 39 publications
11
94
0
1
Order By: Relevance
“…This result is line with the reduction of liver index and hepatomegaly ( Figure 2), and the restoration of pathological changes such as inflammatory cell infiltration and necrosis in hepatic tissues ( Figure 6). It is also consistent with our recent report that taraxasterol could inhibit inflammatory cytokines TNF-a and IL-6 production in mice with alcoholic liver injury [17]. It indicated that taraxasterol could prevent Con A-induced acute hepatic injury by suppressing the secretion of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is line with the reduction of liver index and hepatomegaly ( Figure 2), and the restoration of pathological changes such as inflammatory cell infiltration and necrosis in hepatic tissues ( Figure 6). It is also consistent with our recent report that taraxasterol could inhibit inflammatory cytokines TNF-a and IL-6 production in mice with alcoholic liver injury [17]. It indicated that taraxasterol could prevent Con A-induced acute hepatic injury by suppressing the secretion of pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Namely, taraxasterol exerts the in vitro anti-inflammatory and immunomodulatory activity by inhibiting inflammatory cytokine and mediator production via regulating NF-jB and MAPKs signalling pathways [12,13], and exhibits the in vivo protective effects in various animal models of inflammation including LPS-induced mouse endotoxic shock [14], ovalbumin-induced mouse allergic asthma [15] and adjuvantinduced rat arthritis [16]. Our recent study has also shown that taraxasterol possesses the protective effects on alcoholic liver injury in mice by exerting anti-oxidative stress and antiinflammatory response via CYP2E1/Nrf2/HO-1 and NF-jB signalling pathways [17]. However, it is unknown whether taraxasterol possesses protective effects against immune-mediated hepatic injury and its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, up‐regulated HO activities by IL‐1β suppressed CYP2E1 expression in rat liver (Kudo and Kawano, ). Moreover, taraxasterol, natural terpene compounds in Chinese herbal medicine, can delay and reduce alcoholic liver damage (Bai et al, ) and also inhibited the EtOH‐induced up‐regulation of CYP2E1, with increased Nrf2 and HO‐1 expression (Xu et al, ). These data suggested the possibility of that up‐regulated HO‐1/2 by 5‐ALA/SFC suppressed CYP2E1 expression and directly protect against gut leakage, liver inflammation, and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the above studies, numerous plants are utilized in folklore medicine and as such are thoroughly investigated for their use in prevention or treatment of ethanol-induced liver injury. Some of these natural products like taraxasterol exhibit their protective potential against ethanol-induced liver damage because they regulate different signaling pathways like NF-kB and CYP2E1/Nrf2/HO-1 in mice models (Xu et al, 2018). Studies also showed that Monolluma quadrangula (Forssk.)…”
Section: Preclinical and Clinical Research Based On Ethnopharmacologimentioning
confidence: 99%